Sustaining hope: A narrative inquiry into the experiences of hope for nurses who work alongside people living with HIV in Ghana - Gideon L. Puplampu; Vera Caine; Jean D. Clandinin (Wiley, 2020)
Abstract Aim In this research, we explored how nurses working in HIV care in Ghana live and work with hope. Background Nurses who work with people living with HIV have concerns about their well‐being and quality of life. They also complain of stress‐related workload due to high nurse-patient ratio. The study sought to examine the experiences of nurses in Ghana and the ways that hope is intertwined with their experiences in working with people living with HIV. Design This study was a narrative inquiry study. Narrative inquiry is a collaborative way to inquire into participants' experiences in the three‐dimensional spaces of temporality, sociality and place. Methods We engaged with five nurses who work in an acute care setting where their primary focus is to provide care to people living with HIV. We engaged in six to eight conversations with each participant over several months. We asked participants to describe memories of significant experiences in their past and present lives, and share experiences that they would describe hopeful in their HIV nursing practice. Results In this narrative inquiry study, four resonant threads emerged and included: (a) becoming a nurse for people living with HIV took time; (b) experiences of practising with hope were important; (c) faith in God, allowed them to gain strength, which was connected to hope; and (d) learning to live with hope was shaped by childhood experiences.